Autonomous Multi-Trophic Observations of Productivity and Export at the Australian Southern Ocean Time Series (SOTS) Reveal Sequential Mechanisms of Physical-Biological Coupling - Trull, Thomas W.; Jansen, Peter; Schulz, Eric; Weeding, Ben; Davies, Diana M.; Bray, Stephen G. (Frontiers in Marine Science, 2019)
The timing of pelagic spring blooms has received attention to understand controls on open ocean productivity and its potential responses to climate change. Many studies have relied on surface chlorophyll (Chl) to define bloom initiation because of its availability from satellite observations, but this has limited utility because it ignores the full water column budget and because biomass represents only the small residual term in the balance between production and loss. Additional important measures include net community production (NCP) which determines maximal energy available to fuel phytoplankton and higher trophic level biomass accumulations, and particulate organic carbon export (POC flux) which determines the distribution of this energy across pelagic, mesopelagic and benthic communities. Here, we present high temporal resolution records for the winter to spring transition (July–December 2012) obtained from moored sensors at SOTS in the Subantarctic Zone (SAZ) south of Australia. Measurements included physical drivers (temperature, salinity, surface mixed layer depth, currents, wind speeds, insolation, and air-sea heat fluxes) and biological responses (Chl from fluorescence and light attenuation, NCP from O2/N2 ratios and nutrient concentrations from an autonomous water sampler, POC flux from sediment traps, and zooplankton abundances from four-frequency acoustic backscatter profiles). These observations provide a phenology across the four trophic levels (NPZD) commonly used in ocean biogeochemical models. Chl column inventories began to increase in early winter while mixed layers were still deepening, and were accompanied by increases in NCP. Acoustic metrics for grazing pressure were very low at this time. In contrast, surface Chl did not increase until later when stratification developed. The levels of spring NCP were relatively high and balanced by sinking particle fluxes close to global median values, despite the relatively low surface biomass levels. Overall this phenology suggests that the extent of exchange with SAMW waters via deep mixing is a key driver of the seasonality of production, support of higher trophic levels, and the mediation of pelagic-benthic coupling, and occurs sequentially via trophodynamic (de-coupling of production and grazing) and physical (stratification) mechanisms.